Cultural travel and migrancy the artistic representation of globalization in the electronic media of West Java - Jurriens, Edwin 1972- (Leiden, The Netherlands KITLV Press, 2004)
It describes artistic approaches to globalization, one of the problems that has benn felt most pressing during the late New order and early Reformation. Situating itself at this remarkable turning-point in Indonesian history, it shows that local artists have not been mere victims or products of globalization, but virtual migrants who self-consciously steer the electronic media on their worldwide travels. The book gives an analysis of relevant case-studies and historical debates on culture and representation in Indonesia and the West, and also provides a overview of early developments and recent trends in the Indonesian and West Javanese media landscapes. With its focus on Sundanese language and culture, it is a pioneering and gab-filling complement to the existing literature on media, which has predominantly dealt with national and international, rathe than regional or local, cultural contexts.
I. Introduction -- II. Travel and migrancy -- Cultural travel and postmodernism -- Migrancy, the third world canon, and popular culture -- Post colonialism and neocolonialism -- III. Global presentation and representation -- Parody, hyperrealism, and the end of representational art -- Pastiche and the (re)birth of representational art -- Interactivity, virtual reality, and the interplay between fiction and reality -- Mediation and performance -- Conclusion -- IV. The regional, the national, and the global in Indonesian politics and cultural debates -- Regional regulations 6 and 7 -- The national cultural policies of Soekarno and Soeharto -- The 'Polemik kebudayaan' of the 1930s -- Contextuality -- Sundanese speech levels and feudalism -- Conclusion -- The West Javanese television, radio, and cassette scene State-owned television in Indonesian and West Java -- The legislative and institutional development of radio in Indonesia -- Indonesian private radio and globalization: the production of news and the segmentation of the market -- Radio stations in Bandung that give special attention to Sundanese culture -- Cassette companies in Bandung that deal with regional culture -- Cassettes in Indonesia and the problem of piracy -- Conclusion -- VI. The television series Inohong di Bojongrangkong -- Te work of Ading -- Globalization and the generation gap -- Religion -- Love, dreams, and social criticism -- Inohong di Bojongrangkong and TVRI Bandung -- Conclusion -- VII. The musical genre of pop Sunda -- The early development of pop Sunda -- The pop Sunda compositions of Nano Suratno -- Sundanese pop music, syncretism, and postcolonialism -- The pop Sunda compositions of Doel Sumbang -- The musical history of Bimbo -- Conclusion -- VIII. The radio programme Dongeng plesetan -- The structure of Dongpless -- The introduction of Dongpless -- The theme story and wise lesson of Dongpless -- Dongpless and Sundanese culture in the era of globalization -- Theatre-in-mind and the humour industry -- Conclusion -- IX. Further thoughts on travel and migrancy -- Social criticism and the reformation -- Global objects and modes of presentation and representation -- Local aspects of migrancy -- Migrancy, postcolonialism, and the third world canon.
Originally presented as the author's thesis (Ph. D.)--Universiteit Leiden, 2001.
Includes bibliographical references (pages [189]-202) and index.
Keywords: Mass media -- Indonesia -- Java; Globalization; Indonesia -- Politics and government -- 1966-1998.